2008
DOI: 10.3354/ame01167
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microbial interactions on the susceptibility of Karenia spp. to algicidal bacteria

Abstract: A bacterial strain (D38BY) belonging to the family Flavobacteriaceae and antagonistic towards an algicidal bacterium (strain S03; Flavobacteriaceae) was isolated from a culture of the red tide dinoflagellate Karenia brevis that had previously been characterized as resistant to attack by strain S03. This antagonistic bacterium increased the survival time of otherwise susceptible, bacteriafree K. brevis cultures in a concentration-dependent manner during exposure to the algicidal bacterium. Experimental evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Cytophaga -like bacteria have been found in Lake Constance, the Mindelsee and the Meldsee (SW Germany) (48). Both Cytophagales and Flavobacteriales have been associated with harmful algal blooms (49) based on their algicidal activity and antagonism towards other bacteria (51). Within the order of Sphingobacteriales , one doubleton was affiliated with Candidatus ‘ Aquirestis calciphila ’.…”
Section: Resultsmentioning
confidence: 99%
“…Cytophaga -like bacteria have been found in Lake Constance, the Mindelsee and the Meldsee (SW Germany) (48). Both Cytophagales and Flavobacteriales have been associated with harmful algal blooms (49) based on their algicidal activity and antagonism towards other bacteria (51). Within the order of Sphingobacteriales , one doubleton was affiliated with Candidatus ‘ Aquirestis calciphila ’.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies, for instance, have described algicidal bacteria that are only effective on a specific genus or species of algae (Fukami et al, 1992;Doucette et al, 1999), while others target a broader range of algal classes (Imai et al, 1995;Lovejoy et al, 1998;Kang et al, 2008;Roth et al, 2008a). The mode of activity can also vary such that direct cell-to-cell contact is necessary for algicidal activity in some bacterial species (Kim et al, 1998;Roth, 2005;Roth et al, 2007Roth et al, , 2008b, while other algicidal bacteria have been found to secrete bioactive compounds with varying effects on the target algal species (Lovejoy et al, 1998;Doucette et al, 1999;Lee et al, 2000;Skerratt et al, 2002;Kang et al, 2008;Kim et al, 2008;Mayali et al, 2008). For example, Roth et al (2007) found that direct contact with the dinoflagellate Karenia brevis was required for algicidal activity of Flavobacteriaceae strain S03, which induced cell lysis after 24 h exposure.…”
Section: Introductionmentioning
confidence: 96%
“…In the specific case of K. brevis , the most comprehensive study of the associated microbial community was conducted almost two decades ago using classical bacteriological methods (Buck & Pierce, 1989). Since then, investigators have used molecular techniques to classify and characterize algicidal bacteria active against this dinoflagellate (Doucette et al , 1999; Mayali & Doucette, 2002; Roth et al , 2008a, b) and have documented a complex relationship between algicidal bacteria and antagonistic (against the algicidal bacteria), potentially co‐occurring microorganisms (Roth et al , 2008a). Moreover, the isolation of algicidal bacteria from waters with and without detectable K. brevis cells suggests that such strains are part of the ambient microbial community and likely increase in abundance when exposed to their target algal cells.…”
Section: Introductionmentioning
confidence: 99%